2021
DOI: 10.3389/fimmu.2021.744129
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Cancer: Interpreting the Differential Bioactivities of Its Pentameric and Monomeric, Modified Isoforms

Abstract: C-reactive protein (CRP) was first recognized in the 1940s as a protein that appeared in blood during acute episodes of infectious disease. Its presence and pharmacodynamics were found in essentially all diseases that involved tissue damage and inflammation. Identified as a major component of the innate, unlearned immunity, it became a useful diagnostic marker for the extent of inflammation during disease exacerbation or remission. Efforts to define its true biological role has eluded clear definition for over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 66 publications
(93 reference statements)
2
38
0
Order By: Relevance
“…The importance of this finding is highlighted by the findings that mCRP was involved in the pathological process after acute myocardial infarction. 14,31 We and other studies further illustrated that increased localization of mCRP was observed in ischemic stroke or the infarcted myocardium after myocardial infarction. 18,32,33 Here, we further demonstrated that mCRP increased and prolonged the duration of proinflammatory cells in infarcted myocardium after MI through the JNK pathway.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The importance of this finding is highlighted by the findings that mCRP was involved in the pathological process after acute myocardial infarction. 14,31 We and other studies further illustrated that increased localization of mCRP was observed in ischemic stroke or the infarcted myocardium after myocardial infarction. 18,32,33 Here, we further demonstrated that mCRP increased and prolonged the duration of proinflammatory cells in infarcted myocardium after MI through the JNK pathway.…”
Section: Discussionmentioning
confidence: 74%
“…Monomeric CRP (mCRP) can be dissociated from its pentamer (pCRP) after binding to activated platelets, apoptotic/necrotic cells, or microparticles (MPs). 13,14 However, it has distinct antigenicity-expressing neoepitopes differing from pCRP. This conformation rearrangement results in significant changes different from the biological activities of CRP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other pathologies such as cancer, the roles of pCRP and mCRP have also been described [ 49 ]. However, neither study conducted on SLE patients have reported the role of CRP according to its structure.…”
Section: Discussionmentioning
confidence: 99%
“…CRP can also foster the formation of the tumor microenvironment (TME) ( 60 , 61 ), which might impair the effect of ICIs. What is more, CRP is an indicator of body damage ( 62 ). It means that, compared with patients with low pretreatment CRP level, patients with high pretreatment CRP level perhaps have worse health and cancer circumstances, which will also affect the effectiveness of ICIs.…”
Section: Discussionmentioning
confidence: 99%